2011
DOI: 10.1002/adsc.201100211
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Chloride as an Efficient Catalyst for Selective Transformations of Indoles in the Presence of a Keto Carbonyl Group

Abstract: Catalysis by manganese chloride tetrahydrate was found to be effective for the selective transformation of indoles, with which the desired acid-catalyzed reaction could be promoted and, at the same time, a side reaction that also needs assistance of acid, the electrophilic reaction of indole with the co-existing keto carbonyl group, does not occur. Some acid-catalyzed reactions, such as the ring-opening reaction of 2-alkoxy-3,4-dihydropyran with indole, and transesterification of b-keto ester with an alcohol t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…For safety and environmental reasons, we continued the reactions with ethanol. Further investigation revealed that the reaction was also affected by the other parameters including catalyst amount, temperature, and reaction time, and the optimal conditions should be 1.2 mol % of LS-Sc I, 808C, and 8 h (entries [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For safety and environmental reasons, we continued the reactions with ethanol. Further investigation revealed that the reaction was also affected by the other parameters including catalyst amount, temperature, and reaction time, and the optimal conditions should be 1.2 mol % of LS-Sc I, 808C, and 8 h (entries [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…This type of reaction is an acid-catalyzed reaction, but proved to be very sensitive to the acid strength of the catalyst. [16] Previously, it has been successfully performed in the presence of manganese(II) halides, such as MnCl 2 and MnBr 2 . [17] However, these catalysts cannot be recycled after the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been reported for the incorporation of the bis(aryl) functionality into target molecules. A protocol involving the disubstitution of acetal 3 with indole by employing a manganese catalyst was reported by Gu and co‐workers in 2011 (Scheme , top) 4. The catalytic disubstitution of aromatic and aliphatic ketones, aldehydes and ethers has also been previously reported by a number of groups 5.…”
Section: Introductionmentioning
confidence: 92%
“…2‐Alkoxy‐3,4‐dihydropyrans were considered as AXB3 s because these compounds are not stable under acidic conditions, and tend to undergo hydrolysis to release an aldehyde group . This unique reactivity enabled the establishment of some synthetic methodologies, which were able to access some valuable molecules, such as 2‐functionalized 1,3‐dicarbonyl compounds, and densely substituted 1,3‐dienes .…”
Section: Masked Axb3 Smentioning
confidence: 99%